Review of qualification and modeling for radiation-induced polymer degradation - Chen, Tianyi; Chang, Tzu-Yi; Konstanczer, Brooke A.; Mostaan, Matin A.; Palmer, Camille J. (Frontiers in Nuclear Engineering, 2023)
Polymeric materials have multiple potential applications in nuclear power reactors including advanced and small modulus reactors, in addition to their extensive usage in safety electronic cables in the existing light water reactors. Through the qualification programs, knowledge accumulates about the polymer degradation kinetics under gamma-irradiation environment to facilitate the development of service-life predictive models. This paper aims to promote mechanistic-based predictability as a new approach to the qualification of polymeric components. Reviewed in this article are the current qualification standards and procedures, the current understandings of the degradation mechanisms, and kinetic models applicable to accelerated experiments for qualification.